Poverty and Income Inequality: Markets and Governments in the International Economy. - Thanawala, Kishor (Journal of Income Distribution®, 1998)
Increases in aggregate national income are not always accompanied by reductions in levels of poverty or by decreases in the magnitudes of Gini coefficients. The Kuznets “Inverted U” hypothesis (Kuznets, 1955, 1963) was based on statistical data relating to several of the contemporary developed countries. But it seems that a similar inverted-U relationship between per capita income and Gini coefficient may form a viable hypothesis on the global level. If so, economic progress measured in terms of per capita income does not, in practice, result in people having greater freedom because increase in per capita income does not necessarily decrease the level of poverty rate and therefore does not always reduce the constraint imposed by the need to satisfy basic wants. This paper discusses some empirical and normative aspects of global poverty and income distribution and the role that markets and governments play in the international economy.